Writing Systems and Their Use An Overview of Grapholinguistics - Meletis, Dimitrios (Trends in Linguistics. Studies and Monographs [TiLSM], 2022)
This book provides a comprehensive overview of the interdisciplinary field of grapholinguistics, treating questions concerning both the structure and use of writing systems by complementing the linguistic main perspective with psycholinguistic and sociolinguistic angles. Core concepts and ideas are defined and discussed on the basis of a broad variety of writing systems, building a comparative framework useful for studying any writing system.